A Machine Learning Framework for Classifying Thermal Stress in Bean Plants Using Hyperspectral Data - Osco, Lucas Prado; Moriya, Érika Akemi Saito [UNESP]; de Lima, Bruna Coelho; Ramos, Ana Paula Marques [UNESP]; Júnior, José Marcato; Gonçalves, Wesley Nunes; de Castro Jorge, Lúcio André; Liesenberg, Veraldo; Li, Jonathan; de Araújo, Ademir Sérgio Ferreira; Imai, Nilton Nobuhiro [UNESP]; de Araújo, Fábio Fernando (MDPI, 2025)
Rising global temperatures pose a significant threat to agricultural productivity, making the early detection of plant stress crucial for minimizing crop losses. While hyperspectral remote sensing is a powerful tool for monitoring plant health, the precise spectral regions and most effective machine learning models for detecting thermal stress remain an open research question. This study presents a robust framework that utilizes eight state-of-the-art machine learning algorithms to classify the reflectance response of thermal-induced stress in two cultivars of bean plants. Our controlled experiment measured hyperspectral data across two growth stages and three stress conditions (pre-stress, during stress, and post-stress) using a spectroradiometer. The results demonstrate the high performance of several algorithms, with the Artificial Neural Network (ANN) achieving an impressive 99.4% overall accuracy. A key contribution of this work is the identification of the most contributory spectral ranges for thermal stress discrimination: the green region (530–570 nm) and the red-edge region (700–710 nm). This framework is a feasible and effective tool for modelling the hyperspectral response of thermal-stressed bean plants and provides critical guidance for future research on stress-specific spectral indices.